Flexibility with a Purpose: Constructing the Legitimacy of Spatial Governance Partnerships. (July 2014) - Lau, Mandy
This paper explores the relationship between flexibility in spatial governance partnerships and their legitimacy. While partnerships have become increasingly prevalent, questions have been raised about their accountability or 'input' legitimacy. However, recent research highlights how multiple norms of legitimacy exist and how flexible delivery of aspired outcomes may confer 'output' legitimacy to governance processes. This paper explores these issues through examining the delivery of a major urban extension at the edge of Cambridge City, in the East of England. It makes the case that a particular dimension of flexibility, namely flexibility in resource deployment, has been crucial to delivering outcomes underpinned by the shared vision of sustainable communities. This suggests that future research on partnerships could benefit from a more refined analysis of the different ways in which flexibility is exercised and how these may enhance or detract from the legitimacy of partnership arrangements.